Review on Role of Shukra Dushti (Vitiation of Semen) in Male Infertility and its Management (International Journal of Ayurveda and Pharma Research, 2022)
Infertility is an indeterminate universal issue affecting humanity. It is noticed in approximately 60-80 million couple worldwide among which 40-50% of infertility is estimated to be due to male factors. Male infertility was remarked in Ayurveda as Klaibya and Anapathya. A separate branch as Vajeekarana (Aphrodisiac therapy) was established among eight branches of Ayurveda, emphasizing the awareness of physiology of Shukradhatu (Sperm) and its role in Reproduction along with the measures to procreate children. Shukradushti/Retodushti (vitiation of Semen) occurs due to congenital and acquired factors leading to defective formation or ejaculation of Shukra by vitiation of Tridoshas (three biological humors), resulting in Klaibya (Male Infertility). The clinical diagnosis of Retodushti (vitiation of semen) by clinical signs and symptoms and Retopareeksha (Semen Analysis) is essential for the management of Klaibya, by utilizing drugs possessing Vrushya (Aphrodisiac) Shukrajanana (Spermatogenic), Shukrashodhana (semen purifier) properties and diet-lifestyle modifications. Literature pertaining to Shukradhatu, Shukradushti, Klaibya, Vaieekarana from Ayurvedic classical literatures and reputed journals were referred to gather information. The mention of Retopareeksha in the era of absence of microscope for diagnosis of Shukradushti shows the awareness on the importance of male infertility in the Ancient period.